A Study on Health Science Students’ Perception of Active Teaching and Learning Methodologies for Creating Excitement in Basic Science Classrooms - Anshoo Agarwal; S. Anil Mohan Rao (Archives of Current Research International, 2018)
Background: The aim of our study was to assess the conventional approach of education as well as to propose other suitable education means that can be endeavored in conveying facts to the students. Fundamentally, giving education must comprise two chief sections, which is sending and receiving information. Eventually, an educator attempts his best to convey information as the way he comprehended it. The practice of novel approach in scholastic organizations has the possibility not only to advance teaching, but also to embolden individuals, build up supremacy and insights the endeavor to accomplish the human improvement goal for the nation. Teaching practices in advanced tutoring are progressively under the limelight and it is indeterminate in certain shares, if conventional approach is in fact as effectual as they are supposed to be. Since the excellence of teaching is essential to a career accomplishment, it is significant to probe an integer of approaches and procedures. The purpose of novel instruction and teaching approach is crucial if we are to influence and stimulate an outlook of education as well as keenness on the part of students, for education while at colleges and undeniably for life -time knowledge. Aim and Objectives: To analyze the perception of students regarding active learning methodologies (Case-based learning (CBL) /group seminars/role play/teaching using flash cards & interactive CD-ROMs) in basic science courses in Medical and Health University. Results: A survey based studied was done in medical and health sconces university in UAE involving medical, dental, nursing and pharmacy students.60 % of the students in all University felt that the didactic lectures are their preferred methodology to learn.30% of the students stated that they like the best teaching methodology to be the ‘Case based learning’. Others preferred (15 %) Problem Based learning while 10% ,8% and 6% liked best teaching methodology to be the group seminars, teaching using flash cards & interactive CD-ROMs, and role play respectively. Rest had no preference for any specific teaching methodology.